2013
DOI: 10.11607/jomi.2614
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Dynamics of Healing at the Tissue-Implant Interface by Means of Microcomputed Tomography and Functional Apparent Moduli

Abstract: Purpose It is currently a challenge to determine the biomechanical properties of the hard tissue–dental implant interface. Recent advances in intraoral imaging and tomographic methods, such as microcomputed tomography (micro-CT), provide three-dimensional details, offering significant potential to evaluate the bone-implant interface, but yield limited information regarding osseointegration because of physical scattering effects emanating from metallic implant surfaces. In the present study, it was hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In the first period, there was intense osteoblastic activity, observed through immunohistochemical analysis, which resulted in greater bone formation on the last assessed period, with almost total closure of critical bone defects. In the speculation about clinical applicability, maturation of bone tissue, an important factor for primary stability in the installation of dental implants [26,27] demonstrated through immunohistochemistry, increased osteocalcin expression for the CLN group at 40 days compared to 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…In the first period, there was intense osteoblastic activity, observed through immunohistochemical analysis, which resulted in greater bone formation on the last assessed period, with almost total closure of critical bone defects. In the speculation about clinical applicability, maturation of bone tissue, an important factor for primary stability in the installation of dental implants [26,27] demonstrated through immunohistochemistry, increased osteocalcin expression for the CLN group at 40 days compared to 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 While we did not perform specific biomechanical testing in this study, we noted that BIC, BVF, TMD, and BMD have strong and moderately strong correlation with the functional apparent modulus, which indicates that histology and microCT data are parallel with mechanical test data, as we have previously reported. 27,30,31 Based on this model, we chose the experimental approach and time points of 10, 14, and 28 days to study effects of the sclerostin antibody on bone formation and dental implant osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…However, micro-CT has several drawbacks. First, artifacts around the metal implant decrease the accuracy of micro-CT results 23 , 24 . Schouten et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the potential of this method for evaluating osseointegration 3 , 12 22 . However, the accuracy of micro-CT-based quantitative evaluation may be affected by unavoidable metal scatter surrounding the titanium implant due to the implant material 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%